Factors Associated With Severity of COVID-19 Disease in Vaccinated Patients - Bahar, Tamanna; Rahman, Shaila; Anne, Rifat Taher; Chowdhury, Zulfia Zinat; Hossain, Mohammad Murad; Sanzida Akter; Mohammad Ali; Amit Wazib (Journal of Dhaka Medical College, 2024)
Background: Vaccines are considered the most promising approach for restraining the COVID- 19 pandemic. We aimed to identify the disease profile and risk of severe disease despite vaccination. Methods: A cross-sectional study was done from June 2021 to August 2021 in the COVID-19 dedicated hospitals in Dhaka. Total 169 RT-PCR positive adult patients were enrolled by a purposive sampling method who had completed two vaccine doses of COVID-19. Disease profile and severity was identified according to the national guideline of Bangladesh. Results: Of the 169 patients, 19 (11%) had severe diseases. The mean age of the study participants was 50.46 (±14.03) year. The mean age of severely diseased patients was higher than that of non-severe disease 62.63 (±8.27) vs 48.91 (±13.86), p-value <0.0001. The overall mortality was 8 (4.7%). In univariate analyses, being elderly (e”60years) (cOR 6.14, 95% CI 2.09-18.03; p-value <0.0001) and male (cOR 5.06, 95% CI 1.13-2274; p-value <0.02 and having DM (cOR 32.94, 95% CI 4.28-253.69; p-value <0.0001, HTN (cOR 2.91, 95% CI 1.05-8.07; pvalue < 0.034, OAD (cOR 3.47, 95% CI 1.09-11.07; p-value < 0.044, IHD (cOR 7.54, 95% CI 2.67-21.31; p-value <0.0001, and CKD (cOR 26.43, 95% CI 4.69-148.92; p-value <0.0001were identified as factors related to severe disease of COVID-19. In multivariate analyses, DM (aOR 13.9, 95% CI 1.5-130.1; p-value <0.021, OAD (aOR 7.9, 95% CI 1.2-50.1; p-value <0.03, IHD (aOR 7.4, 95% CI 1.6-34.4; p-value < 0.011, and CKD (aOR 41.9, 95% CI 2.6-667.4; p-value < 0.008 were independently associated with severe disease. Conclusion: Vaccines against COVID-19 are showing a significant decrease in severity disease. Control of chronic diseases, exposure prevention and mass vaccination should be the main concern to mitigate the severity. J Dhaka Med Coll. 2022; 31(2) : 220-225